Human sustainability: Collaborative learning for health and well-being in the academy - Edith Gnanadass; Wendy Griswold; Donna Menke (Adult Education Research Conference, 2021)
This roundtable will help educators develop a holistic focus on their mental, physical, and spiritual well-being to engage fully with learners (hooks, 1994). Faculty affected by the global pandemic and stressors of academia took control of their work-life balance crucial to human sustainability (Sheared, 2019). Researcher One participated in a diabetes prevention program, experienced improved health and overall well-being, then used a community education model to share her learning with colleagues. The researchers are exploring their informal self-directed learning process using Prochaska and DiClemente’s (1982) transtheoretical model, Lave and Wenger’s (1991) community of practice, and Kolb’s (1984) experiential learning model.
Keywords: Human sustainability; transtheoretical model; community of practice; experiential learning; learning for health and well being